Stainless Steels for Medical and Surgical Applications 2003
DOI: 10.1520/stp11169s
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Products Generated from Mechanically Assisted Crevice Corrosion of Stainless Steel Orthopaedic Implants

Abstract: Accelerated corrosion of metallic implants in vivo can generate both soluble and insoluble products that can be detected locally and systemically. Retrieved stainless steel implants for trauma fixation or spinal instrumentation demonstrate iron and chromium-containing solid products of corrosion deposited around corroded modular junctions and as phagocytosable particles in the adjacent tissues. In some cases, the resulting adverse local tissue reaction has been associated with pain, inflammation and osteolysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Estudos in vitro sobre a corrosão de aços inoxidáveis em soluções fisiológicas mostram que elementos tóxicos como Cr, Ni e Mo estão presentes, tanto em solução, como nos produtos de corrosão. A presença destes íons pode resultar no aparecimento de reações inflamatórias e, em casos extremos, na perda do implante (Fathi et al 2003;Urban et al 2003).…”
Section: Vi)unclassified
“…Estudos in vitro sobre a corrosão de aços inoxidáveis em soluções fisiológicas mostram que elementos tóxicos como Cr, Ni e Mo estão presentes, tanto em solução, como nos produtos de corrosão. A presença destes íons pode resultar no aparecimento de reações inflamatórias e, em casos extremos, na perda do implante (Fathi et al 2003;Urban et al 2003).…”
Section: Vi)unclassified
“…Fracture fixation plates and syringe needles made of 316LV have been used, but removal of the plates has been required due to corrosion. 11 Moreover, the modulus of elasticity of the material is above 200 GPa, which makes the material unsuitable for reconstruction prostheses as it is intended to remain permanently inside the body. Cobalt chromium alloys used for biomedical applications include cobalt-chromium-molybdenum (CoCrMo; ASTM F75) and cobalt-nickel-chromiummolybdenum (CoNiCrMo; ASTM F562).…”
Section: Metals and Metal Alloysmentioning
confidence: 99%
“…with mechanically assisted crevice corrosion of orthopedic implants (Crevice Corrosion section) (Goldberg, Buckley, Jacobs, & Gilbert, 1997;Urban et al, 2003). However, the oxide on 316L stainless steel implants has been shown to become depleted in Ni and Mn, indicating preferential release of these ions into the surrounding fluid (Sundgren, Bodö, Lundström, Berggen, & Hellem, 1985).…”
Section: Alloysmentioning
confidence: 99%
“…Elevated concentrations of Cr have been measured in the serum of patients with modular hip implants made from stainless steel Urban et al, 2003) and in the serum and urine of patients with hip implants containing Co-Cr alloy components (Black, Maitin, Gelman, & Morris, 1983;Jacobs et al, 1998). In addition, a study involving dogs found evidence of Cr in the bone adjacent to Co-Cr bone plates implanted for up to 17 months (Castleman, Motzkin, Alicandri, & Bonawit, 1976).…”
Section: Explantsmentioning
confidence: 99%